miR-3188 inhibits hepatitis B virus transcription by targeting Bcl-2 - Wang, Shijie; Xie, Ying; Liu, Fufei; Wang, Jianrong; Yang, Yinghao; Wang, Junxue; Wang, Yongxiang; Hang, Xiaofeng (Archives of virology, 2024)
Transcription of the covalently closed circular DNA (cccDNA) of hepatitis B virus (HBV) is subject to dual regulation by host factors and viral proteins. MicroRNAs (miRNAs) can regulate the expression of target genes at the post-transcriptional level. Systematic investigation of miRNA expression in HBV infection and the interaction between HBV and miRNAs may deepen our understanding of the transcription mechanisms of HBV cccDNA, thereby providing opportunities for intervention. miRNA sequencing and real-time quantitative PCR (qRT-PCR) were used to analyze miRNA expression after HBV infection of cultured cells. Clinical samples were analyzed for miRNAs and HBV transcription-related indicators, using qRT-PCR, enzyme-linked immunoassay (ELISA), and Western blot. miRNA mimics or inhibitors were used to study their effects on the HBV life cycle. The target genes of miR-3188 and their roles in HBV cccDNA transcription were also identified. The expression of 10 miRNAs, including miR-3188, which was significantly decreased after HBV infection, was measured in clinical samples from patients with chronic HBV infection. Overexpression of miR-3188 inhibited HBV transcription, whereas inhibition of miR-3188 expression promoted HBV transcription. Further investigation confirmed that miR-3188 inhibited HBV transcription by targeting Bcl-2. miR-3188 is a key miRNA that regulates HBV transcription by targeting the host protein Bcl-2. This observation provides insights into the regulation of cccDNA transcription and suggests new targets for anti-HBV treatment.